Remain silent - Steiner, Susie, 1971- (Steiner, Susie, 1971- Manon Bradshaw novel., 2020)
"Newly married and navigating life with a toddler as well as her adopted adolescent son, Fly Dent, Manon Bradshaw is happy to be working part-time in the cold cases department of the Cambridgeshire police force, a job which allows her to "potter in, coffee in hand and log on for a spot of internet shopping--precisely what she had in mind when she thought of work-life balance." But beneath the surface Manon is struggling with the day-to-day realities of what she assumed would be domestic bliss: fights about whose turn it is to clean the kitchen, the bewildering fatigue of having a young child in her forties, and the fact that she is going to couple's counseling alone because her husband feels it would just be her complaining. But when Manon is on a walk with her two-year-old son, Teddy, in a peaceful suburban neighborhood and discovers the body of a Lithuanian immigrant hanging from a tree with a mysterious note attached, she knows her life is about to change. She is suddenly back on the job, full-force, trying to solve the suicide - or is it a murder - in what may be her most dangerous and demanding case yet"--